SIFAT FISIKOKIMIA DAN HEDONIK COOKIES OATS DENGAN PENGGUNAAN TEPUNG KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Frederick Wijaya; Antonius Hintono; Yoyok Budi Pramono (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
This research was to determine the effect of using red dragon fruit peel flour for each concentration used in oats cookies towards antioxidant activity, aw, texture, colour and hedonic. The benefit of this research is to get the best oats cookies by utilizing the waste by-product red dragon fruit peel and increasing the characteristics of products as functional food. The experimental design was used was a completely randomized design (CRD) with 4 treatments and 5 replication. The treatments consisted of T0 as the control variable, T1, T2 and T3 each of which had a ratio concentration of red dragon fruit peel flour and wheat flour of 0%:100%, 20%:80%, 40%:60%, and 60%:40%. The results showed that the treament of using 20% red dragon fruit peel flour had a greater antioxidant activity, colour and preference than the control treatment which has the potential as a functional food.